A clinical-physiological assessment of Dexalgin anaesthesia efficacy in patients with injuries - Lysenko, Viktor; Orlov, Gennadiy; Kamalov, Oleg; Karpenko, Evgeniy; Zgola, Iryna (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
The article gives a clinical-physiological assessment of the efficacy of anaesthesia in patients with injuries. In order to control pain syndromes during the postoperative period, a large number of drug preparations were suggested: narcotic and nonnarcotic analgetics, neuroleptics, spasmolytics, etc. Taking into account the character of pain, its intensity and the area of a surgical intervention during slightly and moderately traumatizing operations in orthopaedics and traumatology, it is possible to use nonsteroid anti-inflammatory drug preparations, such as Dexalgin (one of its advantages consists in the absence of any considerable side effects). Thirty-two patients were examined at Sytenko Institute of Spine and Joint Pathology of the Academy of Medical Sciences of Ukraine (the City of Kharkiv). Both groups, 15 and 17 people, received at their postoperative period respectively Morphine and Dexalgin. Anaesthesia was assessed by the visual analogue scale, and histamine was studied simultaneously. The data were statistically assessed by calculating the mean value (X) and its error (Sx). Student’s test was used for determining the significance of differences between the above groups. The performed study demonstrated efficacy and good prospects of using Dexalgin for anaesthesia in traumatological clinical practice after minimally and moderately traumatizing operations.